Work-Related Stress and Company Size – It Industry in Croatia - Kostelac, Mateo; Kokot, Karolina (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Work-related stress is an inevitable aspect of the business environment, making studies in this field crucial for both scientific and practical contributions. This paper examines the causes and levels of stress among employees in Croatia's IT industry. The study aims to define stress levels in the IT sector and investigate how company size impacts stress. The stress levels were assessed through a questionnaire using the PSS-10 scale for measurement. The research sample comprised 121 respondents, and the data was statistically analyzed through ANOVA. The results did not indicate any significant differences in stress levels based on company size, suggesting that company size does not impact stress levels. The study identified that the most common causes of stress in the Croatian IT industry were: the number of job tasks, interpersonal relationships among coworkers, and limited promotion opportunities. Recommendations for reducing stress levels in the Croatian IT industry include managing work-life balance and providing continuous management support.